Paediatric Analgesia during Inguino-Scrotal Surgery- A Pilot Study - Brendan Stern; Manisha Shah; Kumarvel Veerappan; Shirley Chan (Global Journal of Anesthesiology - Peertechz Publications, 2016)
Introduction: There are many different analgesic methods used for children undergoing inguinoscrotal surgery. Research suggests that caudal analgesia reduces the need for postoperative pain relief in these children compared with regional techniques but may increase the risk of motor block and urinary retention. This can be problematic given that these procedures are commonly performed as day cases. Primary Aim: Assess post-operative pain requirements of the three different analgesic methods used at Medway Maritime hospital in paediatric surgery patients undergoing inguino-scrotal surgery.  Secondary Aim: Assess whether there were any differences between these methods in rates of post-operative complications, including time before spontaneous leg movement, micturition, rates of nausea and vomiting and time to discharge.  Methodology: This study prospectively recruited paediatric surgery patients undergoing elective day case inguino-scrotal surgery at MMH between May and July 2015.  Three analgesic methods were employed: Group 1.IG/IH under ultrasound guidance (10mls, 0.25% levobupivicaine) + direct intra-operative GF block (2mls, 0.25% levobupivicaine) Group 2.Caudal (1.5ml/kg, 0.125% levobupivicaine) + clonidine (1.5mcg/kg) Group 3.Local infiltration (2mg/kg, 0.5% levobupivicaine) with intra-operative morphine (100 micrograms/kg). Results: 26 patients (24 boys, 2 girls) were recruited over a time period of two and a half months. Only one patient from group 1 and one patient from group 2 had positive pain scores, whereas five patients in group 3 had positive pain scores. There was no clinically significant difference in time before first leg movement or micturition between the three groups.  Conclusion: Our pilot study suggests that a direct intra-operative block of the GF nerve with a pre-operative IG/IH nerve block provides the same level of postoperative analgesia as a caudal block but without increasing post-operative complications.